Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Ulang Seblak Duar Bangkalan - Nadila Islamia; Hadi Purnomo (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this study determines the effectiveness of productquality, price, and promotion of the decision repurchase in Seblak DuarBangkalan. This research usesquantitative methods. The sampling techniqueused non-probability sampling with purposive sampling as a sampling method,this study uses of 100 sample respondents. The population in this study areSeblak Duar Bangkalan customers who have bought. The result of this studyis the product quality and promotion variables that have a partial effect onrepurchase decisions, while the price does not have partially affect ofrepurchase decisions.Keywords: Product Quality, Price, Promotion, Repurchase Decision